Sino-Orbital Aspergillosis in a Kidney Transplant Recipient - Christian Maalouli; Julien De Greef; Thierry Duprez; Arnaud Devresse; Caroline Huart; Maëlle Coutel; Nathalie Demoulin; Leïla Belkhir; Nada Kanaan (Case Reports in Transplantation)
Sino-orbital aspergillosis is a rare and severe infection mostly seen in immunocompromised individuals in which diagnosis may be challenging with potentially life-threatening consequences. Infection usually starts in the paranasal sinuses with secondary spreading to the adjacent orbits. Here, we report the case of a kidney transplant recipient who presented with proven invasive sino-orbital aspergillosis resulting in irreversible loss of vision despite surgical management and antifungal therapy. We review the literature with a focus on clinical presentation, diagnostic tools, and recommended treatment in the context of kidney transplantation.